2013
DOI: 10.1111/j.1464-410x.2012.11657.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of transperineal template‐guided prostate biopsy in 409 patients

Abstract: What's known on the subject? and What does the study add?• With an aging population and routine use of PSA testing, there is an increase in men undergoing biopsy to assess for prostate cancer. The most common route for accessing the prostate is through the rectum, which potentially exposes the patient to otherwise innocuous Enterobacteriaceae. The rising incidence of extended-spectrum beta-lactamase has been linked to a rise in post-TRUS biopsy infection rates internationally.• The study describes an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 45 publications
6
55
1
Order By: Relevance
“…The lack of postbiopsy infection or sepsis is important in contrast to the 3%-11% infection rates previously reported for transrectal US, especially in light of rising antibiotic-resistant infections after transrectal biopsies (46)(47)(48). It can be performed in men with difficult or impossible rectal access, such as patients who have undergone proctocolectomy or those with rectal stenosis from prior radiation treatment (49).…”
Section: Discussionmentioning
confidence: 89%
“…The lack of postbiopsy infection or sepsis is important in contrast to the 3%-11% infection rates previously reported for transrectal US, especially in light of rising antibiotic-resistant infections after transrectal biopsies (46)(47)(48). It can be performed in men with difficult or impossible rectal access, such as patients who have undergone proctocolectomy or those with rectal stenosis from prior radiation treatment (49).…”
Section: Discussionmentioning
confidence: 89%
“…Studies including more than 100 cases have reported detection rates of 35.6–54.8% [9, 10, 18, 22, 28, 29]. Although the technique of TTSB and the number of biopsy cores varied among these studies, the cancer detection rate in repeated biopsy patients was almost similar.…”
Section: Discussionmentioning
confidence: 95%
“…Prostate volume has been considered a negative predictor of positive PCa by transperineal prostate biopsy in other reports [10, 28]. Merrick et al used a 24-region technique with a median (mean, range) of 50.0 (51.1, 24–66) biopsy cores for patients whose mean prostate volume was 78.6 ml [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a biopsy-based multivariable analysis, the repeat biopsy procedure itself was not associated with a greater risk of serious complications requiring hospital admission compared to the initial biopsy session 59 . In patients undergoing transperineal PB, the reported incidence of infections and sepsis is close to zero (0-0.2%), given the avoidance of bacterial contamination (which is common during transrectal access), as well as the limited number of cores taken when performing transperineal MRI-guided in bore biopsy [8][9][10]13,[25][26][27]29,[63][64][65][66][67] . Although data are currently limited, it is uncertain whether the lower incidence of infectious complications after MRI-targeted PB could be related to the sampling route (i.e.…”
Section: Infectious Complications and Hospitalization Rates After Promentioning
confidence: 99%